Miestų medinės architektūros išsaugojimo galimybės - Lukšionytė, Nijolė (Journal of Architecture and Urbanism, 2011)
Wooden architecture in cities: opportunities for preservingInstitutions for Lithuania’s heritage protection have been declaring the necessity of preserving wooden architecture since 2002; however, there have been very few realistic results. Although the Vilnius City Municipality initiated a strategic programme for saving wooden architecture, there have been no tangible results to date.The purpose of this article s to analyse the needs and opportunities for preserving wooden architecture in Kaunas. Wooden buildings such as small manor and garden estate houses, villas, cottages, summer homes, rental houses and residential military and railway complexes have survived in Kaunas. Representative buildings of all these types need to be preserved in all parts of Kaunas. These reflect the juncture of professional and ethnic traditions in cities, estates and villages. Therefore such buildings are exceptional at conveying local identity.The 2009 educational project carried out at the Faculty of Arts of Vytautas Magnus University revealed that the survival of wooden houses largely depends on the motivation of their owners. The most important condition for preserving wooden architecture is to attract the owners of these buildings to join with the supporters of this architectural heritage. Consultations on the maintenance of such buildings to retain the heritage must be organised. The community interested in rehabilitation of wooden structures could generate and share information in a virtual environment.Article in Lithuanian.Santrauka. Paveldosaugos institucijos Lietuvoje nuo 2002 m. deklaruoja medinės architektūros išsaugojimo būtinumą, tačiau realių rezultatų pasiekta labai nedaug. Vilniaus miesto savivaldybės iniciatyva parengta medinės architektūros apsaugos strategijos programa kol kas nedavė apčiuopiamų rezultatų. Straipsnis skirtas Kauno medinės architektūros išsaugojimo poreikių ir galimybių analizei. Kaune išliko medinių dvarelių, sodybinių namų, vilų, kotedžų, vasarnamių, nuomojamų namų, kariškių ir geležinkeliečių gyvenamųjų kompleksų. Reikėtų išsaugoti šių tipologinių grupių architektūros reprezentantus visose miesto dalyse. Jie atspindi profesionaliosios ir etninės (miesto, dvaro, kaimo) tradicijų jungtį ir dėl to yra išskirtiniai lokalinio tapatumo perdavėjai. VDU Menų fakultete 2009 m. vykdytas edukacinis projektas atskleidė, jog medinių namų išlikimas daugiausia priklauso nuo savininkų motyvacijos. Savininkų patraukimas į medinio paveldo rėmėjų pusę laikytinas svarbiausia išsaugojimo sąlyga. Būtina organizuoti konsultavimą apie paveldui palankią namų priežiūrą ir tvarkymą. Medinių namų atgaivinimu suinteresuota bendruomenė galėtų kurtis ir dalintis informacija virtualioje aplinkoje.Reikšminiai žodžiai: mediniai namai, architektūros paveldas, Kaunas.First Publish Online: 22 May 2013